2021
DOI: 10.1093/nar/gkab603
|View full text |Cite
|
Sign up to set email alerts
|

Mutually exclusive substrate selection strategy by human m3C RNA transferases METTL2A and METTL6

Abstract: tRNAs harbor the most diverse posttranscriptional modifications. The 3-methylcytidine (m3C) is widely distributed at position C32 (m3C32) of eukaryotic tRNAThr and tRNASer species. m3C32 is decorated by the single methyltransferase Trm140 in budding yeasts; however, two (Trm140 and Trm141 in fission yeasts) or three enzymes (METTL2A, METTL2B and METTL6 in mammals) are involved in its biogenesis. The rationale for the existence of multiple m3C32 methyltransferases and their substrate discrimination mechanism is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 39 publications
2
23
0
Order By: Relevance
“…The two protein molecules bind distinct regions of tRNA Ser (the long variable arm and anticodon loop, respectively), but they do not display steric hindrances. Additionally, both studies 15 , 26 have suggested a tRNA-dependent interaction between hSerRS and hMETTL6; thus, these possible interactions might be insufficient for a stable complex in the absence of tRNA, which awaits further experimental verification.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The two protein molecules bind distinct regions of tRNA Ser (the long variable arm and anticodon loop, respectively), but they do not display steric hindrances. Additionally, both studies 15 , 26 have suggested a tRNA-dependent interaction between hSerRS and hMETTL6; thus, these possible interactions might be insufficient for a stable complex in the absence of tRNA, which awaits further experimental verification.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…The assays followed the same procedure as described 26 . The reaction mixes were incubated for 5 min before the reactions were stopped.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Saccharomyces cerevisiae (S. cerevisiae ), the m 3 C methyltransferase Trm140 mediates modification of both cytoplasmic tRNA Thr/Ser whereas in Schizosaccharomyces pombe (S. pombe ) two alternative enzymes, Trm140 and Trm141, install m 3 C 32 modifications in cytoplasmic tRNAs Thr and tRNAs Ser respectively 30 , 37 . The mammalian homologues of the S. pombe proteins, METTL2 (with paralogues A and B in humans) and METTL6 are likewise responsible for installing these modifications into the human tRNAs Thr and tRNA Ser 38 41 . The m 3 C 32 modification is also present in mammalian tRNA Arg(CCU) and tRNA Arg(UCU) , and METTL2A/B, together with the cofactor protein DALRD3, has recently been identified as the methyltransferase responsible for introducing these modifications 40 .…”
Section: Introductionmentioning
confidence: 99%